The Influence of Hard Skills K3, Soft Skills and Work Environment on the Behavior of Implementing K3 in Welding Practices of Mechanical Engineering Study Program Students in Vocational High Schools in North Sulawesi - Parsaoran Tamba,; Hendro M. Sumual, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Vocational High Schools (SMK) are educational institutions that prepare graduates to be ready to work, so that there are more practical lesson hours compared to theory lesson hours. With so many hours of practice, vocational school students are very vulnerable to work accidents. Preventive measures against work accidents, when students carry out work practices, must implement K3. The behavior of implementing K3 can be influenced by the K3 hard skills mastered by students, the soft skills possessed by students and the practical work environment. Through this research, we want to find out how much influence K3 hard skills, soft skills, and work environment have on students' behavior in implementing K3. The student population as respondents was 73 students taken from vocational schools that have a mechanical engineering study program, namely SMKN 2 Bitung, SMKN 2 Manado, SMK Garuda Bitung and SMK Cokroaminoto Kotamobagu. By using a saturated sampling technique, the entire population was taken as a sample with a sample size of 73 students. The analysis technique in this research uses regression and correlation analysis techniques, and it is revealed that there is an influence between hard skills on the behavior of implementing K3 of 0.69 (69%), there is an influence between soft skills on the behavior of implementing K3 of 0.76 and there is an influence The relationship between work environment and behavior of implementing K3 is 0.85 (85%). With these findings, it is hoped that vocational schools will focus more on improving occupational safety and health (K3) learning materials so that students have optimal K3 hard skills. Providing lessons or other activities that can develop students' soft skills and improve the comfort of the welding work practice environment must be taken into account, such as noise levels, ventilation, lighting, room cleanliness and preparing complete personal protective equipment (PPE).